Глибокі нейронні мережі для вирішення задач класифікації зображень звикористанням бібліотек keras та tensorflow - Норматова, Т. В. (ХНУРЕ, 2019)
This work is devoted to solving the problem of image classification based on deep learning. The task was classifyimagesinto two categories using a convolutional neural network (CNN). For this research, KerasPythonlibrary with TensorFlow library was used. As a result, convolutional neural network was created which detects the presence of a cat or a dog on the input image and assigns it the certain category. In the future, this CNN can be replaced by a pre-trained neural network from Kerasto improve classification accuracy.